Bitter fame : a life of Sylvia Plath - Stevenson, Anne, 1933 Jan. 3- (Boston : Houghton Mifflin, 1989)
A biography of the poet from New England, describing her life, accomplishments, and her suicide at thirty
"A Peter Davison book."
Includes index.
Bibliography: p. 359-386.
Keywords: Plath, Sylvia; Poets, American -- 20th century -- Biography